Mathematical Modeling Of The Quality Indicators Of TwoLayer Knitted Fabrics Obtained On Flat Two-Needle Knitting Machines With The Needles Placed In A Rubber Arrangement (Texas Journal of Engineering and Technology, 2023)
In the article presents the results of mathematical modeling of the quality indicators of double-layer knitted fabrics on double-bed flat knitting machines and the law of the influence of the structure of knitted fabric on the consumption of weed is determined